Implementasi Vigenére Cipher pada AJAX (Asynchronous Javascript and XML) - Redy Santiawan, Ida Bagus; Mahendra Darmawiguna, I Gede; Antara Kesiman, Made Windu (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This studi aimed to : (1) designing Vigenére Cipher in AJAX (Asynchronous Javascript and XML), (2) implementing Vigenére Cipher in AJAX (Asynchronous Javascript and XML). In designing and implementing the system, it was used 2 main methods in implementation of the encryption and decryption. On the encryption method, plaintext as input and ciphertext as output, and then on the decryption method ciphertext as input and plaintext as output. The test has been done with network sniffing ie capture the data passing on the network. In designing and implementing the application design, it was used a waterfall method which is usually called as a classic life cycle model. This is a classic model which creates the software systematically and sequentially that includes some stages namely: (1) requirements definition, (2) system and software design, (3) implementation and unit testing, and (4) integration and system testing. The implementation and testing in this study was a Vigenére Cipher Aplication that were using a PHP for server side and a Javascript for client side. Based on the data of the system performance test, obtained that the system can hide the data sent to the network.